Autologous Microfractured and Purified Adipose Tissue for Arthroscopic Management of Osteochondral Lesions of the Talus - D'Ambrosi, Riccardo (J Vis Exp, 2018)
In recent years, regenerative techniques have been increasingly studied and used to treat osteochondral lesions of the talus. In particular, several studies have focused their attention on mesenchymal stem cells derived from adipose tissue. Adipose-derived stem cells (ADSCs) exhibit morphological characteristics and properties similar to other mesenchymal cells, and are able to differentiate into several cellular lines. Moreover, these cells are also widely available in the subcutaneous tissue, representing 10 - 30% of the normal body weight, with a concentration of 5,000 cells per gram of tissue. In the presented technique, the first step involves harvesting ADSCs from the abdomen and a process of microfracture and purification; next, the surgical procedure is performed entirely arthroscopically, with less soft tissue dissection, better joint visualization, and a faster recovery compared with standard open procedures. Arthroscopy is characterized by a first phase in which the lesion is identified, isolated, and prepared with microperforations; the second step, performed dry, involves injection of adipose tissue at the level of the lesion. Between January 2016 and September 2016, four patients underwent arthroscopic treatment of osteochondral lesion of the talus with microfractured and purified adipose tissue. All patients reported clinical improvement six months after surgery with no reported complications. Functional scores at the latest follow-up are encouraging and confirm that the technique provides reliable pain relief and improvements in patients with osteochondral lesion of the talus.